Women's HIV disclosure to the dentist: Does frequent contact matter?. (13th October 2020) - Parish, Carrigan L.; Feaster, Daniel J.; Pereyra, Margaret R.; Alcaide, Maria L.; Weber, Kathleen M.; Cohen, Mardge H.; Levin, Susanna; Gustafson, Deborah; Merenstein, Daniel; Aouizerat, Bradley E.; Donohue, Jessica; Webster‐Cyriaque, Jennifer; et al.
Abstract: Objectives: Research has shown inconsistent patterns of patients' HIV serostatus disclosure to their dentists. Common barriers to disclosure have included confidentiality concerns, fear of treatment refusal, and discrimination. This study evaluated the prevalence of HIV serostatus disclosure to the dentist, whether the frequency of dental care utilization is associated with disclosure, and reasons for nondisclosure among women living with HIV. Methods: We administered a cross‐sectional oral health survey to 1, 526 women living with HIV in the Women's Interagency HIV Study including questions regarding HIV serostatus disclosure to dentists. Logistic regression models were used to analyze the association between dental care utilization (at least annually versus less than annually) and HIV serostatus disclosure to dentists. Results: Overall, 83 percent of women reported that they disclosed their HIV serostatus to their dentist. The most common reasons for nondisclosure were: a) the dentist did not ask, b) believing that the dentist did not need to know, and c) not having a consistent dentist. In the multivariable logistic regression model, at least annual dental care utilization, compared to less than annual, led to a 59 percent reduction in the odds of HIV nondisclosure to the dentist. Discussion: Study findings highlight that dentists who see their patients infrequently should consider methods for overcoming barriers to HIV nondisclosure and the possibility that their patient's HIV serostatus is undisclosed. Educating women living with HIV about how disclosure to dentists is a critical component of their dental assessment and treatment, and how preventive dental treatment can improve overall health outcomes, is important.